Moderating work efficiency and performance through best-practice certification: management’s perspective - Saad, Mazni; Ong, Mohd Hanafi Azman; Mohamad Ali, Afiza; Samat, Nusrah; Ahmad, Rohana (IIUM Press, 2020)
This paper examines the urgent need to successfully implement best practice certification when determining an effective economic mechanism for the foodservice industry from the management perspective. The study involved 73 managers of targeted foodservice companies (at a response rate of 92%) who participated in a survey. The 33 best-practice compliant companies and 40 companies still undergoing the certification process formed the sample. The Partial Least Squares Structural Modeling (PLS-SEM) indicates that best-practices had a significant influence on work efficiency and performance in the context of the full sample. The Measurement Invariance Assessment of Composite Model (MICOM) analysis also indicates that the best-practice certification adoption group moderated this relationship between best-practices and work efficiency and performance. However, the results show that the best-practice certified group demonstrated a stronger relationship between food relevant best practices and work efficiency and performance compared to the group undergoing certification. The outcome reveals that embracing best-practice management can lead to a strong systematic approach in enhancing a business operation.